Specificity of Deoxyribonucleic Acid Intercalating Compounds in the Control of Phenylalanine Ammonia Lyase and Pisatin Levels - Hadwiger, Lee A. (1971)
Compounds with planar triple ring systems such as acridine orange, 9-amino acridine, 9-amino-1,2,3,4-tetrahydroacridine (tacrine), 6,9-diamino-2-ethoxyacridine lactate monohydrate (DE-acridine), 6-chloro-9-(3′-diethylamino-2′-hydroxypropylamino) -2-methoxyacridine·2 HCl (CDM-acridine), quinacrine, 6-chloro-9-(4′-diethylamino-1′-methylbutylamino) -2-methoxy-1,10-diazaanthracene (CDM 1,10-diazaanthracene), thionine, azure A, methylene blue, and pyronine Y when applied to excised pea pods were potent inducers of phenylalanine ammonia lyase or of pisatin, or of both. Compounds with an array of structural variation around the planar three-ring system were tested for their ability to induce these responses in pea tissue. In general, dimethylamino, diethylamino, or amino substitutions at position 2 and 6 or an amino (with or without an aliphatic side chain) substitution at position 9 of the three-ring system augmented induction potential. Methyl green, methylene blue, 2,7-diaminofluorene, nile blue, neutral red, pyrogallol red, ethidium bromide, nogalamycin, quinine, chloroquine, spermine, 8-azaguanine, gliotoxin, chromomycin A(3), actinomycin D, and mitomycin C were also potent inducers. The inhibition of phenylalanine ammonia lyase induction by the application of actinomycin D (300 micrograms per milliliter) or 6-methylpurine (1 milligram per milliliter) within 1 hour after inducer application indicated that newly synthesized RNA is necessary for induction. Phenylalanine ammonia lyase induction was also inhibited by cycloheximide (150 micrograms per milliliter).